2012
DOI: 10.1007/s00586-012-2192-4
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement in fusion status assessment after instrumental desis of the lower lumbar spine using 64-slice multidetector computed tomography: impact of observer experience

Abstract: Purpose Persistent lower back pain after instrumental posterolateral desis may arise from incomplete fusion. We investigate the impact of experience on interobserver agreement in fusion estimation. Methods Four independent observers, two residents and two musculoskeletal radiologists, reviewed dedicated lumbar 64-MDCT scans and scored vertebral levels 1-5 after Glassman's grades, 1: solid bilateral fusion, 2: solid unilateral fusion, 3: partial bilateral fusion, 4: partial unilateral fusion, 5: non-fusion. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Visualization of obliteration in the facet joints and bone bridges, for example, is a more suggestive sign that bone fusion has been achieved. 10 In 2005, Glassman et al 9 published a classification system to evaluate the evolution of posterolateral arthrodesis based on 1mm tomographic cuts with sagittal and coronial reconstructions, in order to evaluate consolidation rates in patients submitted to this surgical procedure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visualization of obliteration in the facet joints and bone bridges, for example, is a more suggestive sign that bone fusion has been achieved. 10 In 2005, Glassman et al 9 published a classification system to evaluate the evolution of posterolateral arthrodesis based on 1mm tomographic cuts with sagittal and coronial reconstructions, in order to evaluate consolidation rates in patients submitted to this surgical procedure.…”
Section: Resultsmentioning
confidence: 99%
“…That study, performed using tomography with coronal reconstruction and 1 mm cuts, demonstrated low interobserver agreement. 10,14 In the present study, the analysis method included prior training and images of tomographic cuts reconstructed at each level in the plane that we call the oblique coronal plane, rather than an analysis of the coronal plane for all levels. We believe that this measure increases the sensitivity of the interpretation of the condition of the fusion, especially at levels with is greater inclination, such as the lumbosacral transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each patient underwent four CT scans in a 64-channel device with multi-slice volume acquisition in the axial plane 24 at the following established intervals: 45, 90, 180 and 360 days after the initiation of the use of the PEMF-emitting device.…”
Section: Assessment Of Arthrodesis Consolidationmentioning
confidence: 99%
“…28,35 Recent studies comparing the accuracy of CT with surgical exploration for the assessment of lumbar arthrodesis consolidation showed sensitivities of 53% to 63% and specificities of 78% to 86%. 18,35 In our study, we interpreted the presence or absence of fusion using the Glassman method, 24,30 to which we added the correction of the coronal plane at each level of arthrodesis to be studied. 25 The specific orientation of the coronal plane for each level of consolidation assessment makes the interpretation of the Glassman method clearer and more reproducible, especially at levels where there is a greater vertebral slope, as in the lumbosacral transition.…”
Section: Effect Of Pulsed Electromagnetic Field On the Consolidation mentioning
confidence: 99%